Implementation of Driver Briefing Policy in Improving Driver Safety at Multinational Company Workshop in Batam, Indonesia - Rafaelin, Fabiola Frederica; Rifai, Andri Irfan; Isradi, Muhammad; Prasetijo, Joewono (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Work safety is a big responsibility for every company, especially the safety of motorists who operate within the Multinational Company Workshop Area. This study examines the extent of employees' understanding of driving safety regulations through driver briefing policies in the Multinational Company Workshop area. Design/methodology/approach: Data were obtained from the results of the questionnaire survey of motorists at Multinational Company Workshop using the questionnaire survey method to find answers. Data retrieval technique using the Purposive Sampling method is collected through online surveys given directly to respondents. After that, the data collection results in Analysis use the web spider method to find the comparison before and after the policy is improved. The population in this study were employees of Multinational Company Workshop in Batam with 70 respondents. Findings: Based on a survey conducted by many employees, many still need to become more familiar with the driving regulations within the Multinational Company Workshop Area. However, some employees already understand and understand the content of the safety briefing themselves. Research limitations/implications: The implementation of research in this paper is tried as much as possible by the intentions and objectives of the research and does not damage the company's image. Data collection in this study was based only on the questionnaire results, so there might have been fewer objective elements in the filling process, such as concurrent mutual filling in the questionnaire. Practical implications: This driver briefing policy applies to creating a healthy and safe work environment to reduce the probability of work accidents or diseases due to negligence resulting in demotivation and deficiency. Originality/value: This paper is an original work Paper type: Research paper